The Effectiveness of Police Forces Through the Centuries: the Evolution of the Training Process in a Contemporary Social Context - Milojević, Saša M.; Milojković, Boban; Janković, Bojan (NBP. Nauka, bezbednosti, policija, 2025)
By researching the emergence and development of police training, he considers how, throughout history, the structure and organization of police forces were shaped, with special emphasis on the processes of education, permanent training and professional development. The evolution of police training in response to dynamic social change and growing demands for professionalism, specialization and certification are being considered. Approaches to training in different countries are analyzed, showing how national and international factors shape educational methods and goals. The paper also sheds light on how theoretical knowledge and practical skills in training contribute to the effectiveness and efficiency of police work in modern society. The paper aims to provide insight into key trends and challenges in police training, with the perspective of further improvement and adaptation of educational strategies to respond to the demands of the modern age.
Keywords: police training; professional development; national and international educational standards; specialization in police forces; modernization of educational methods